FATTY ACID COMPOSITION OF Heterobranchus GEOFFROY SAINT-HILAIRE, 1808 SPECIES FROM RIVER GALMA, ZARIA, KADUNA STATE, NIGERIA - YASHIM, E. Y; AUTA, J.; AKEN’OVA, O. L.; ADEYINKA, I. A.; ATAWODI, E.; ONIYE, S. J. (Nigerian Journal of Fisheries, 2021)
The fatty acid profiles of Heterobranchus species were investigated from River Galma, Zaria Kaduna State, Nigeria. Fresh samples of H. bidorsalis and H. longifilis obtained from the water body were subjected to Soxhlet method of oil extraction using n-hexane as solvent and Gas Chromatography Mass-Selective Detection (GCMSD; Agilent Technology) for the detection of fatty acids present in the fish species. The resulting profiles revealed 17 fatty acids in H. bidorsalis and 19 fatty acids in H. longifilis, whereas monounsaturated fatty acid (MUFA) forms the bulk of the fatty acid in both species, saturated (SFA), as well as polyunsaturated (PUFA) fatty acids, were also identified. More PUFA was found to be present in H. bidorsalis than in H. longifilis with the reverse occurring in MUFA. Dominant among the identified and qualitatively measured fatty acids include Myristic C14:0, Lauric C12:0, Pentadecylic C15:0, Palmitic C16:0, Margaric C17:0, Palmitoleic acid C16:1(n7), Oleic Acid C18:1(n-9), Fumaric acid C18:1(n-11), and Linoleic C18:2(n-6). Essential fatty acids which are important sources of nutrients promoting good health, prevention, and healing of diseases were identified from the species.